FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI INSTANSI PEMERINTAHAN KOTA JAMBI TAHUN 2021 - Harissa, Nuri Putri; Aurora, Wahyu Indah Dewi; Rahman, Ave Olivia (Scientific Of Environmental Health and Diseases, 2022)
ABSTRACTBackground: The problem of exclusive breast milk coverage that still does not reach the target and the factor ofworking mothers is one of the obstacles of mothers in providing exclusive breast milk. Purpose of this study to findout the relationship of Factors that affect exclusive breastfeeding mothers working in the Jambi City GovernmentAgency in 2021.Method: This study is a quantitative study using cross sectional design with validated questionnaires. A sample of126 respondents was taken by consecutive sampling method in working mothers in Jambi City GovernmentAgencies that meet the criteria for inclusion and exclusion. Analysis of the relationships between variables is doneusing the chi-square test.Results: There is a meaningful relationship between education towards exclusive breastfeeding (p=0.030),between attitudes toward exclusive breastfeeding (p=0.034). While there is no meaningful relationship betweenthe mother's age to exclusive breastfeeding (p=0.813), knowledge of exclusive breastfeeding (p=0.645), facilitiesfor exclusive breastfeeding (p=0.565), husband's support for exclusive breastfeeding (p=0.357) and health workers'support for exclusive breastfeeding (p=0.576).Conclusion: There is a meaningful relationship between education and attitude towards exclusive breastfeeding.While there is no meaningful relationship between the mother's age, knowledge, facilities, husband’s support andhealth worker’s support for exclusive breastfeeding in working mothers.Keywords: Exclusive Breast Milk, Working Moms, AgenciesABSTRAKLatar Belakang: Permasalahan cakupan ASI Eksklusif yang masih kurang mencapai target dan faktor ibu bekerjayang menjadi salah satu hambatan ibu dalam memberikan ASI secara eksklusif. Tujuan penelitian ini untukmengetahui hubungan Faktor-faktor yang MempengaruhiPemberian ASI Eksklusif pada Ibu Bekerja di Instansi Pemerintahan Kota Jambi Tahun 2021.Metode: Penelitian ini merupakan penelitian kuantitatif menggunakan rancangan cross sectional dengankuesioner yang telah divalidasi. Sampel sebanyak 126 responden diambil dengan metode Consecutive Samplingpada ibu bekerja di Instansi Pemerintahan Kota Jambi yang memenuhi kriteria inklusi dan ekslusi. Analisishubungan antara variabel dilakukan dengan menggunakan uji chi-square.Hasil: Didapatkan hubungan yang bermakna antara jenjang pendidikan terhadap pemberian ASI eksklusif(p=0,030) dan antara sikap terhadap pemberian ASI eksklusif (p=0,034). Sedangkan tidak didapatkan hubunganyang bermakna antara umur ibu terhadap pemberian ASI eksklusif (p=0,813), antara pengetahuan terhadappemberian ASI eksklusif (p=0,645), antara ketersediaan fasilitas terhadap pemberian ASI eksklusif (p=0,565),antara dukungan suami terhadap pemberian ASI eksklusif (p=0,357) dan antara dukungan tenaga kesehatanterhadap pemberian ASI eksklusif (p=0,576).Kesimpulan: Didapatkan hubungan bermakna antara jenjang pendidikan dan sikap terhadap pemberian ASIEksklusif. Sedangkan antara umur ibu, pengetahuan, ketersediaan fasilitas, dukungan suami dan dukungantenaga kesehatan terhadap pemberian ASI eksklusif pada ibu bekerja tidak didapatkan hubungan yang bermakna.Kata kunci: ASI Eksklusif, Ibu Bekerja, Instansi